Comparative study of mouse models of atopic dermatitis - Siqi Ye; Lian Zhu; Tao Ruan; Jinjing Jia; Xiumei Mo; Fenggen Yan; Junfeng Liu; Yu Zhang; Dacan Chen (Heliyon)
Atopic dermatitis (AD) is a chronic, recurrent inflammatory disease. Animal models are important for studying disease mechanisms and identifying new therapeutic agents. However, owing to AD heterogeneity and complexity, there is currently no mouse model that can fully simulate human AD. We searched experimental articles published between 2017 and 2021 to identify the most suitable AD mouse model. We summarized and compared 614 articles, including details on mouse strains, sex, age, irritants, modeling cycles, and spontaneous mouse models. BALB/c mice (45.3 %) were the most commonly used. Generally, 4–8-week-old mice were used, and 44 irritants were identified. The most common irritant was 2,4-dinitrochlorobenzene (DNCB), followed by Dermatophagoides farinae mite antigen extract (DfE). The modeling period was generally 21–30 days. There is no perfect AD animal model, and we suggest selecting the most suitable AD model based on previous research or using two or more models to meet experimental requirements. When exploring allergies and T cell differentiation, it is recommended to use DNCB and DfE separately or in combination to stimulate BALB/c mice and NC/Nga mice for constructing AD models. If researchers want to explore the differentiation of Th17 and Th2 cells, the use of flaky tail mice is recommended. If researchers want to conduct research from the perspective of transcriptomics, it is recommended to increase the construction of IL-23 injected mice.